Matla': Astronomical Rising Points dan Problematika Keberlakuan Matla' - Zulfa, Faizatuz; Royyani, Muh. Arif (Lembaga Yasin AlSys, 2023)
The development and progress of Astronomy at this time began with observations of the natural world by medieval astronomers, even earlier. In ancient times, researchers made observations of celestial bodies such as stars, moon and sun only with the naked eye. Observations continue to be made starting from the rising and setting of celestial bodies which can eventually be used as a reference for time, used to determine the Qibla direction, and with regard to other Muslim worship. So the purpose of this study is to find out about matla' in two categories, namely the history of the emergence of matla' and discussing the validity of matla' in relation to the beginning of the lunar month. The data collection method was obtained from literature study, namely by taking data from books and scientific records related to the theme of the discussion, especially matla'. This paper concludes that the study of ancient people's observations of the circulation of the earth, moon and sun, as well as nature and everything in it, as well as studies of the remains of astronomical instruments owned by these Islamic scientists and astronomers, made the treasures of Islamic astronomy stay alive and thrive. Then it can be understood that matla' is the limit of the validity of rukyat. The problem of matla' raises differences of opinion among the people. In essence, there are two opinions regarding this matla'. The first group argues that the implementation of rukyat is for all Muslims around the world. Meanwhile, the second group argues that the implementation of rukyat is only for Muslims in an area. Both from the first and second opinions both have strong arguments.